2006
DOI: 10.1007/s11255-006-9109-2
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in the elderly with chronic kidney disease

Abstract: Considering the aging dialysis population of today, increasing our knowledge about the nature, diagnosis and the treatment of bone mineral density (BMD) problems in end-stage renal disease (ESRD) patients deserves more attention. Osteoporosis is basicly defined as a decrease in bone mass. Large epidemiological studies in general population have identified several risk factors for osteoporosis including advancing age, female gender, white race, decreased calcium intake, gastric acid suppression therapy, sedenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 61 publications
1
24
0
3
Order By: Relevance
“…The results of our study demonstrate a positive correlation between BMD at the regions of the proximal femur and weight or body mass index. Low body weight is known to be a risk factor for low BMD in the general population and several studies in CKD patients observed the same relationship [40][41][42][43] .…”
Section: Both Gender Females Malesmentioning
confidence: 77%
“…The results of our study demonstrate a positive correlation between BMD at the regions of the proximal femur and weight or body mass index. Low body weight is known to be a risk factor for low BMD in the general population and several studies in CKD patients observed the same relationship [40][41][42][43] .…”
Section: Both Gender Females Malesmentioning
confidence: 77%
“…The most significant problems associated with bone metabolism in hemodialysis patients are secondary hyperparathyroidism, osteomalacia, and adynamic bone disease. 2 They can each be accountable for low bone mineral density (BMD). Moreover, low BMD is also associated with elevated fracture risk.…”
Section: Introductionmentioning
confidence: 99%
“…No dose adjustment is necessary in patients with mild or moderate renal failure (ClCr greater than or equal to 30 ml/min), although there may be increased risk of renal toxicity in elderly patients or in patients simultaneously receiving other nephrotoxic drugs [31,32].…”
Section: Treatment Of Decreased Bone Mass In Chronic Kidney Disease Smentioning
confidence: 99%
“…But in patients with CrCl < 30ml/min renal elimination is decreased, the concentration being approximately two times higher than in patients with normal renal function, so it is advisable to reduce the dose by half [31][32][33][34].…”
Section: Treatment Of Decreased Bone Mass In Chronic Kidney Disease Smentioning
confidence: 99%